Ontología y gnoseología del capitalismo de Isaac Ilich Rubin: "Ensayos sobre la teoría marxista del valor" - Armesilla Conde, Santiago J. (Nómadas. Critical Journal of Social and Juridical Science, 2012)
This concise essay attempts to show why Isaak Illich Rubin is, until today, the best interpreter, commentator and developer of The Capital of Karl Marx, understanding Marx’s work as an ontology and a gnoseology of the capitalist economic system. To do this, we analyze the relations existing between Marx, Rubin and the theory of science of the Spanish Marxist philosopher Gustavo Bueno. In this way, we can interpret the work “Essays on Marxist theory of value” also as an ontology and a gnoseology of capitalism.
Keywords: Rubin; capitalism; theory of labor-value; Marx; Politic Economy; Marginal Utility; ontology; gnoseology; science; technology; technique; scientific truth; Gustavo Bueno; Theory of Categorial Closing; circularism; socialism; Philosophical Materialism.